Pain Tolerance in Chronic Pain Patients Seems to be More Associated with Physical Activity than with Depression and Anxiety - Skogberg, Olof; Karlsson, Linn; Börsbo, Björn; Arendt-Nielsen, Lars; Graven-Nielsen, Thomas; Gerdle, Björn; Bäckryd, Emmanuel; Lemming, Dag (Journal of rehabilitation medicine, 2022)
Objective: To explore the associations between habitual self-reported physical activity, pain sensitivity and patient-reported outcomes (including pain intensity) in patients with chronic pain.Design: Cross-sectional, experimental study.Subjects: Patients (n = 78), age range 18–65 years, with different chronic pain conditions (> 3 months) were compared with age- and sex-matched healthy controls (n = 98).Methods: Multivariate correlations between self-reported physical activity, pressure pain sensitivity, and patient-reported outcome measures were assessed.Results: Lower perceived health status (p < 0.001, Cohen’s d = 2.34), higher levels of depression (p < 0.001, Cohen’s d = 1.77), and lower pain tolerance threshold (p < 0.001, Cohen’s d = 1.66) were the most prominent variables discriminating patients from controls. In patients, bivariate and multivariate analyses showed that higher pressure pain tolerance was associated with male sex, lower pain intensity and fewer painful regions, higher self-efficacy and more self-reported physical activity, but not with lower levels of anxiety and depression.Conclusion: Pain tolerance thresholds, as well as degree of depression and perceived health status discriminated between patients and controls, and there was an association between pain tolerance thresholds and level of self-reported physical activity in patients. This study highlights the importance of further research into how increased physical activity may improve pain sensitivity in patients with chronic pain. LAY ABSTRACTPatients with chronic pain and healthy controls were included in this study of the relationships between self-reported physical activity, measurements of sensitivity to pressure pain, and questionnaire data. Pressure pain sensitivity was one of the most important factors discriminating between patients and controls, and there was a significant correlation between pain tolerance threshold and level of self-reported physical activity in patients (i.e. the lower pain thresholds the less physical activity). These results are relevant, as there are only a few previous studies examining the relationship between physical activity in patients with chronic pain and their sensitivity to pressure pain. More research is needed to explore how daily physical activity may improve chronic pain by, for example, increasing patient’s tolerance to pain.